2023
DOI: 10.1371/journal.pgph.0002059
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of populations at risk of sub-optimal dosing of artemisinin-based combination therapy in Africa

Abena Takyi,
Verena I. Carrara,
Prabin Dahal
et al.

Abstract: Selection of resistant malaria strains occurs when parasites are exposed to inadequate antimalarial drug concentrations. The proportion of uncomplicated falciparum malaria patients at risk of being sub-optimally dosed with the current World Health Organization (WHO) recommended artemisinin-based combination therapies (ACTs) is unknown. This study aims to estimate this proportion and the excess number of treatment failures (recrudescences) associated with sub-optimal dosing in Sub-Saharan Africa. Sub-population… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Specifically, our analysis indicated that, in the absence of such tools, end users attributed treatment failures to a broad range of causes, including self-medication, incorrect dosage, and poor compliance. This issue was further underscored in a recent publication by Takyi et al (2023) [22], estimating that one in four people with malaria was at risk of receiving sub-optimal antimalarial drug dosing, potentially leading to treatment failure and an increased risk of resistance to malaria drugs. Despite the lack of robust evidence on the emergence of resistance to ACTs, our survey found that all participants were concerned about the consequences of such resistance on the management of malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, our analysis indicated that, in the absence of such tools, end users attributed treatment failures to a broad range of causes, including self-medication, incorrect dosage, and poor compliance. This issue was further underscored in a recent publication by Takyi et al (2023) [22], estimating that one in four people with malaria was at risk of receiving sub-optimal antimalarial drug dosing, potentially leading to treatment failure and an increased risk of resistance to malaria drugs. Despite the lack of robust evidence on the emergence of resistance to ACTs, our survey found that all participants were concerned about the consequences of such resistance on the management of malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, our analysis indicated that, in the absence of such tools, end-users attributed treatment failures to a broad range of causes, including self-medication, incorrect dosage, and poor compliance. This issue was further underscored in a recent publication by Takyi et al (2023) [22], estimating that one in four people with malaria was at risk of receiving sub-optimal antimalarial drug dosing, potentially leading to treatment failure and an increased risk of resistance to malaria drugs. Despite the lack of robust evidence on the emergence of resistance to ACTs, our survey found that all participants were concerned about the consequences of such resistance on the management of malaria.…”
Section: Discussionmentioning
confidence: 99%